Digital Public Relations in Islamic Boarding Schools: The SANtren Pro-Media Model for Value-Governed Stakeholder Engagement - Aji Wahyudin; Sugeng Listyo Prabowo; Like Raskova Octaberlina; Muhamad Furqon; Okik Dwi Cahyani (Universitas Nurul Jadid, 2025)
Islamic boarding schools, known as pesantren, built their reputation for generations through oral tradition and the personal authority of the kiai, yet digital platforms have moved that reputation into an environment where visibility and responsiveness now shape public trust. This study examines how social-media-based public relations is designed and implemented to strengthen the institutional image of pesantren without weakening their religious identity and hierarchical traditions. A qualitative multisite case study was conducted at two established pesantren in East Java, Indonesia, drawing on interviews, non-participant observation, documents, and platform analytics, and the evidence was analyzed through within-case, cross-case, and triangulation procedures. Findings reveal a shift from oral communication toward formal and value-governed public-relations structures in which creative teams operate under managerial and religious oversight, communication is segmented across platforms for different stakeholders, and content combines trend responsiveness with institutional validation. Social media expands reach, transparency, and stakeholder attachment, but it produces institutionally bounded dialogue rather than fully symmetrical communication. These patterns are synthesized into the six-stage SANtren Pro-Media Model and the Digital Loyalty Loop, both governed by tabligh and amanah as ethical principles. The study implies that pesantren can pursue digital relevance and public accountability while preserving religious identity when digital communication is institutionalized as a professional governance function.